Pension Reform in Southeastern Europe : Linking to Labor and Financial Market Reforms - Holzmann, Robert (World Bank, 2012)
The reform of public pension systems and, more generally, the review of old-age income support are on the reform agenda worldwide. The reform discussion is more intense in countries where population aging is well advanced, including the member countries of the Organization for Economic Co-operation and Development (OECD), much of Latin America, China, Russia, and the former transition economies of Southeastern Europe (SEE). But developing countries in the global South are also awakening to the challenges of aging and old-age income support in view of changing family structures, urbanization, and migration. Over 80 percent of the increase in the numbers of persons age 65 and older up to 2050 will take place in countries with current per capita incomes of US$1,000 and below. Whereas the North grew rich before becoming old, the South risks becoming old before becoming rich. The remainder of the chapter attempts to substantiate this point. The next section briefly describes aging and its fiscal implications in the light of demographic developments in the countries of Southeastern Europe. There follows an outline of the drivers of pension reform that go beyond population aging and have to be understood when choosing among reform options. Subsequent sections take up recent international reform trends and lessons and underline key points concerning the labor market and financial market reforms needed to support pension reform. The chapter ends with some concluding remarks.